Orbital compartment syndrome secondary to subperiosteal abscess initiated by barotrauma. Issue 3 (24th March 2022) - Toh, Zhi Yon Charles; Cameron, Angus
Abstract : This case report demonstrates an unusual complication of bacterial rhinosinusitis, causing orbital compartment syndrome from a presumed barotrauma. We postulate that the patient developed unilateral optic neuropathy, as a result of orbital compartment syndrome, secondary to orbital subperiosteal abscess following direct communication with the ethmoid sinus initiated by barotrauma. It is supported by evidence of a bony dehiscence on the lamina papyracea of the medial orbital wall with sudden onset of pain, proptosis and visual symptoms during flight.